Use of multiple criteria in an ecological assessment of a prairie restoration chronosequence. Issue 1 (25th June 2013) - Hansen, Michael J.; Gibson, David J.; Middleton, Beth
Abstract Questions Was ecological fidelity (structure/composition, function and durability) restored in a series of tallgrass prairie restorations? Which factors influenced success? Can success be assessed in prairie restoration using indices of ecological fidelity? Location Nachusa Grasslands in Lee and Ogle Counties, Illinois, USA. Methods To assess restoration of ecological fidelity, mean coefficient of conservatism (Mean C), floristic quality index (FQI), above‐ground net primary productivity (ANPP), soil bulk density, total soil nitrogen (N) and total soil carbon of 19 restoration sites were recorded from 20 × 50 m modified Whittaker plots across a chronosequence, and compared to benchmark values acquired from both the literature and field observation of remnant prairies. Following assessment, multiple factors were examined through correlation analysis, Akaike's information criterion and multiple regression analysis to determine the relationship of these factors to restoration success. Results All restoration sites attained the benchmark value for Mean C, while only four attained the benchmark value for FQI. Mean C and FQI both decreased across the chronosequence. Frequency of prescribed fire and soil bulk density had significant positive relationships to Mean C. FQI was best explained by the FQI value of the seed mix sown. Thirteen restoration sites attained the benchmark value for ANPP, which remained stable across the restoration chronosequence. Abundance of exotic species and soil drainage had a negative relationship to ANPP. Few restoration sites attained benchmark values for soil bulk density, total N and total carbon, and none of the sites showed a trajectory towards benchmark values across the chronosequence. Conclusions Our study demonstrates that high‐quality seed mixes may aid in establishing prairie restorations with high scores of floristic quality. However, restoration of vegetation does not guarantee the successful restoration of ecological function. Long‐term monitoring is needed to more effectively assess durability and the multiple factors that influence restoration quality. Overall, the three components of ecological fidelity related to structure/composition, function and durability provide a useful framework to assess restoration success and guide management. Our study can serve as a model for future research and assessment of restoration success.